KETAHANAN KELUARGA DALAM MENGHADAPI ANCAMAN BENCANA NON ALAM PANDEMI COVID 19: SEBUAH STUDI KASUS DI KOTA BOGOR - M Maryanti; H Heridadi; Sri Sundari (Republic of Indonesia Defense University, 2021)
The COVID-19 pandemic in Indonesia has a multi-sectoral impact, starting from the health, education, social, economic sectors, to worship activities in the community. The Ministry of Health of the Republic of Indonesia stated that the COVID-19 cases in Bogor City were dominated by family clusters caused by the vulnerability of family resilience. The purpose of this study was to analyze the resilience of families in the city of Bogor in the face of non-natural disasters COVID-19 and the efforts of the Bogor City Government in increasing family resilience. The method used in this study is a qualitative descriptive analysis involving informants from the community and regional apparatus organizations. The analysis in this study uses the theory of family resilience Sunarti (2010) and the theory of disaster management. The results of the study show that family resilience is quite vulnerable during the COVID-19 pandemic, both in terms of physical and economic resilience, as well as social and psychological resilience. The Bogor City Government's efforts to approach the community by initiating various programs to increase family resilience include the establishment of the RW Siaga, the Salur program, and the Foster Family program. However, in practice it is still not effective in increasing family resilience. The recommendation from the research is that there is a need for synergy between policy makers and academics, practitioners, and the community for policy making to increase family resilience.